Occurrence and characteristics of faecal immunochemical screen-detected cancers vs non–screen-detected cancers: Results from a Flemish colorectal cancer screening programme. Issue 2 (March 2020) - van de Veerdonk, Wessel; Hoeck, Sarah; Peeters, Marc; Van Hal, Guido; Francart, Julie; De Brabander, Isabel
Background: Colorectal cancer (CRC) and its precursor lesions are detected at an early stage by CRC screening programmes, which reduce CRC-related mortality. An important quality indicator for CRC screening is the occurrence of interval CRC (IC) between screening rounds. Currently there is no guideline regarding acceptable levels of ICs in CRC screening programmes, and ICs reported in prior work vary considerably. Methods: This study describes the occurrence of screen-detected (SD) CRC and non–screen-detected CRC within the population-based CRC screening programme of Flanders, stratified by multiple variables such as sex, age, tumour location and tumour stage between October 2013 and July 2017. In addition, faecal immunochemical test (FIT) IC proportions over the sum of SD-CRCs and FIT-ICs are calculated, together with FIT sensitivity and programme sensitivity to display the effectiveness of detecting CRC by the screening programme. Results: Of 1, 212, 354 FIT participants, 4094 were diagnosed with SD-CRC, whereas 772 participants were diagnosed with CRC between FIT-screening rounds. Significant associations were shown between people not being SD for CRC and women, older individuals, right-sided tumour location and more advanced tumour stage. Furthermore, a clear distinction was shown between the right-sided and the left-sided colorectum concerning all above-mentioned variables and distributions of tumour stages. Conclusion: The Flemish FIT-interval CRC proportion of 15.9% was within the limits of previously published results. In addition, calculations show that the effectiveness of the screening programme is dependent on tumour location, suggesting that future research should report results stratified by location.